2019
DOI: 10.1088/1741-2552/ab39cf
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing optogenetic stimulation protocols in auditory corticofugal neurons based on closed-loop spike feedback

Abstract: Objective. Optogenetics provides a means to probe functional connections between brain areas. By activating a set of presynaptic neurons and recording the activity from a downstream brain area, one can establish the sign and strength of a feedforward connection. One challenge is that there are virtually limitless patterns that can be used to stimulate a presynaptic brain area. Functional influences on downstream brain areas can depend not just on whether presynaptic neurons were activated, but how they were ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Besides, one would also anticipate that prediction neurons would have their strongest impact when peripheral signals are weak (i.e., the Kalman gain would be highest under these circumstances). Consistent with this idea, previous work has shown that top-down modulation tends to be strongest in broadly tuned neurons [presumably neurons with ambiguous frequency representations (Vila et al, 2019) or when acoustic stimulus amplitude is weak (Jen et al, 1998)]. It may be the case that neurons that are broadly tuned to isolated sounds may be more sharply tuned in other contexts.…”
Section: Conclusion and Future Challengesmentioning
confidence: 69%
See 1 more Smart Citation
“…Besides, one would also anticipate that prediction neurons would have their strongest impact when peripheral signals are weak (i.e., the Kalman gain would be highest under these circumstances). Consistent with this idea, previous work has shown that top-down modulation tends to be strongest in broadly tuned neurons [presumably neurons with ambiguous frequency representations (Vila et al, 2019) or when acoustic stimulus amplitude is weak (Jen et al, 1998)]. It may be the case that neurons that are broadly tuned to isolated sounds may be more sharply tuned in other contexts.…”
Section: Conclusion and Future Challengesmentioning
confidence: 69%
“…Importantly, the specific protocol of electrical stimulation may make a large difference in the impact on subcortical neurons. Small changes in the relative timing of cortical vs. acoustic stimulation, relative amplitudes, pulse rates, etc, can change responses from excitatory to inhibitory, even with optogenetic stimulation (Guo et al, 2017;Vila et al, 2019). Also, many studies have used stimulation paradigms that are really perceptual learning paradigms.…”
Section: Methodological Issues In Top-down Modulation In the Subcortical Auditory Systemmentioning
confidence: 99%
“…Importantly, the specific protocol of electrical stimulation may make a large difference on the impact on subcortical neurons. Small changes in the relative timing of cortical vs. acoustic stimulation, relative amplitudes, pulse rates, etc, can change responses from excitatory or inhibitory, even with optogenetic stimulation (Guo et al, 2017;Vila et al, 2019). In addition, many studies have used stimulation paradigms that are really perceptual learning paradigms.…”
Section: Early Vs Late Top-down Modulationmentioning
confidence: 99%
“…In addition, one would also anticipate that prediction neurons would have their strongest impact when peripheral signals are weak (i.e., the Kalman gain would be highest under these circumstances). Consistent with this idea., previous work has shown that top-down modulation tends to be strongest in broadly tuned neurons (presumably neurons with ambiguous frequency representations (Vila et al, 2019) or when acoustic stimulus amplitude is weak (Jen et al, 1998b)). It may be the case that neurons that are broadly tuned to isolated sounds may be more sharply tuned in other contexts.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…These corticofugal projections likely play a major role in hearing by providing an anatomical substrate for “top-down” information to control early acoustic processing. Indeed, stimulating or silencing the auditory cortex in vivo changes spontaneous and sound-evoked activity throughout the central auditory system (Massopust and Ordy, 1962; Ryugo and Weinberger, 1976; Yan and Suga, 1998, 1999; Nwabueze-Ogbo et al, 2002; Xiao and Suga, 2002; Yu et al, 2004; Nakamoto et al, 2008, 2010; Anderson and Malmierca, 2013; Kong et al, 2014; Vila et al, 2019; Blackwell et al, 2020; Qi et al, 2020), indicating that high-level activity regulates the moment-to-moment function of sub-cortical auditory circuits. However, little is known regarding the biophysical properties of auditory corticofugal synapses, nor do we understand how descending signals are integrated with ascending information.…”
Section: Introductionmentioning
confidence: 99%